Enantioselective Total Synthesis and Structural Revision of Dysiherbol A. Issue 27 (1st June 2021) - Baars, Julian; Grimm, Isabelle; Blunk, Dirk; Neudörfl, Jörg‐Martin; Schmalz, Hans‐Günther
Abstract: A 12‐step total synthesis of the natural product dysiherbol A, a strongly anti‐inflammatory and anti‐tumor avarane meroterpene isolated from the marine sponge Dysidea sp., was elaborated. As key steps, the synthesis features an enantioselective Cu‐catalyzed 1, 4‐addition/enolate‐trapping opening move, an Au‐catalyzed double cyclization to build up the tetracyclic core‐carbon skeleton, and a late installation of the C5‐bridgehead methyl group via proton‐induced cyclopropane opening associated with spontaneous cyclic ether formation. The obtained pentacyclic compound (corresponding to an anhydride of the originally suggested structure for dysiherbol A) showed identical spectroscopic data as the natural product, but an opposite molecular rotation. CD‐spectroscopic measurements finally confirmed that both the constitution and the absolute configuration of the originally proposed structure of (+)‐dysiherbol A need to be revised. Abstract : In a key step of the first enantioselective total synthesis of the anti‐inflammatory marine meroterpene dysiherbol A, the tetra‐carbocyclic core skeleton is set‐up in a unique gold‐catalyzed double cyclization, and the ether bridge of the pentacyclic target structure is spontaneously formed under cyclopropane opening upon deprotection of a late intermediate.